2019
DOI: 10.1111/tpj.14158
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis E2Fc is required for the DNA damage response under UV‐B radiation epistatically over the microRNA396 and independently of E2Fe

Abstract: UV-B radiation inhibits plant growth, and this inhibition is, to a certain extent, regulated by miR396mediated repression of Growth Regulating Transcription factors (GRFs). Moreover, E2Fe transcription factor also modulates Arabidopsis leaf growth. Here, we provide evidence that, at UV-B intensities that induce DNA damage, E2Fc participates in the inhibition of cell proliferation. We demonstrate that E2Fc-deficient plants show a lower inhibition of leaf size under UV-B conditions that damage DNA, decreased cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
(107 reference statements)
4
24
0
Order By: Relevance
“…Interestingly, mutants deficient for histone acetyltransferases showed reduced growth inhibition after UV-B exposure, associated with altered expression of E2F transcription factors (Fina et al, 2017). Consistently, E2Fc know-down lines show less severe reduction of leaf growth in response to UV-B than the wild-type, suggesting that E2Fc could also play a role in the DDR activated by UV light (Gómez et al, 2019), as was previously suggested for the atypical E2Fe (Radziejwoski et al, 2011).…”
Section: Role Of the Plant Ddr In Abiotic Stress Responsessupporting
confidence: 70%
“…Interestingly, mutants deficient for histone acetyltransferases showed reduced growth inhibition after UV-B exposure, associated with altered expression of E2F transcription factors (Fina et al, 2017). Consistently, E2Fc know-down lines show less severe reduction of leaf growth in response to UV-B than the wild-type, suggesting that E2Fc could also play a role in the DDR activated by UV light (Gómez et al, 2019), as was previously suggested for the atypical E2Fe (Radziejwoski et al, 2011).…”
Section: Role Of the Plant Ddr In Abiotic Stress Responsessupporting
confidence: 70%
“…In addition, and as already described in the animal field [113,114], the implication of these cell cycle regulators in DDR has clearly emerged [60]. As expected, a transcriptional control of DDR genes dependant notably on RBR1, E2FA, as well as E2FC, has been observed in Arabidopsis [62,110,111,115]. Also, RBR1 and E2FA have been shown to be recruited directly at the sites of DNA lesions, where they co-localise with γ-H2AX foci in an ATM-and ATR-dependent manner, suggesting their close participation in repair mechanisms [110,111,116].…”
Section: Dreams Upon Dna Damagesupporting
confidence: 64%
“…In addition to the MuvB-core, we decided to also follow up the typical E2F transcription factors. Whereas E2FA ( Horvath et al, 2017 ) and E2FC ( Gómez et al, 2019 ) have previously been shown to be part of the DDR network, the role of E2FB has not yet been explored in detail. When we analyzed seedling roots expressing pgE2FA-3 x vYFP or pgE2FB-3 x vYFP by confocal microscopy after 24 h growth on cisplatin-containing or control plates, respectively, we observed that the overall E2FB signal seemed slightly enhanced after 24 h growth on genotoxin, whereas the E2FA signal was very similar to the signal in roots grown on control plates ( Fig 8A ).…”
Section: Resultsmentioning
confidence: 99%